A MnN4 moiety embedded graphene as a magnetic gas sensor for CO detection: A first principle study - Sarawoot Impeng (2019)
© 2018 Elsevier B.V. The feasibility of using a MnN4 moiety embedded graphene (MnN4-GP) as a gas sensor was investigated by density functional theory calculations. Thirteen gas molecules (CO, CO2, NO, NO2, N2O, SO2, NH3, H2O, H2S, CH4, O2, H2 and N2) were considered. The adsorption behaviors of these gases on MnN4-GP were intensively analyzed in terms of adsorption structure, electronic charge, density of states (DOS), magnetic moments and recovery time. Among thirteen gases, NO, NO2, O2, CO and SO2 adsorbed on MnN4-GP showed strong chemisorption energies, calculated to be −2.30, −1.42, −1.32, −1.11 and −0.51 eV, respectively, while the rest of the gases had physisorption interactions with MnN4-GP. Moreover, the strong chemisorption of the four gases drastically changed the DOS of MnN4-GP and pronounced charge transfer between the adsorbed gas and MnN4-GP. Interestingly, the magnetic moment of MnN4-GP was apparently changed from 3.01 µB to 0.13, 1.04 and 2.01 µB, when it was adsorbed by NO, CO and NO2 gases, respectively, while it was hardly altered by other gases. In addition, the calculated recovery times at 423 K of NO, CO and NO2 are 2.5 × 1014 s, 1.7 s and 8275 s, respectively. Such a short recovery time for CO detection makes MnN4-GP interesting as a sensor. When considering all calculated properties, MnN4-GP is proposed as a promising magnetic sensor for CO detection with high selectivity and high sensitivity.